2021
DOI: 10.15359/ru.35-2.21
|View full text |Cite
|
Sign up to set email alerts
|

Normas que regulan la gestión de clases virtuales de matemáticas en el contexto COVID-19

Abstract: El estudio de las normas que regulan la gestión de clases y negociación de aprendizajes es uno de los temas que ha sido de interés para la comunidad de investigación en educación matemática. En la actualidad, en el contexto de virtualidad motivado por la pandemia por Covid-19, es necesario estudiar el tipo de normas que emergen y regulan las interacciones que se suscitan en las clases de matemáticas. En este artículo, se presentan los resultados de un estudio en el que se caracterizan las normas que regulan la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
1
1
0
3
Order By: Relevance
“…); and in the second type are those that allow promoting learning (e.g., Minitab, R, Microsoft Excel, G*Power, etc.). The above is in accordance with the classification made by Peña, Pino-Fan, and Assis [59] on mediational norms when teaching and learning processes are developed in virtual environments. In this sense, in virtual contexts such as those promoted by COVID-19, the resources and means of an instructional process can be classified into primary and secondary, and the latter are conditioned by the resources and means for virtual connection and interaction.…”
Section: Final Reflectionssupporting
confidence: 87%
“…); and in the second type are those that allow promoting learning (e.g., Minitab, R, Microsoft Excel, G*Power, etc.). The above is in accordance with the classification made by Peña, Pino-Fan, and Assis [59] on mediational norms when teaching and learning processes are developed in virtual environments. In this sense, in virtual contexts such as those promoted by COVID-19, the resources and means of an instructional process can be classified into primary and secondary, and the latter are conditioned by the resources and means for virtual connection and interaction.…”
Section: Final Reflectionssupporting
confidence: 87%
“…This relationship implies that the more competent and confident teachers are in integrating technology, the more likely they are to utilize it effectively in the classroom. Peña et al (2021) found evidence that TPACK explains approximately 46% of the variance in TISE among teachers. The findings imply that teachers with a diverse set of TPACK skills feel more efficacious, leading to more tech-positive learning outcomes for their students.…”
Section: Pedagogical Knowledge Influences Technology Integration Self...mentioning
confidence: 96%
“…En este sentido el sistema normativo está integrado por seis tipos de normas entre las cuales están las correspondientes a las facetas epistémica, cognitivas, afectivas, mediacionales, interaccionales y ecológicas. En tal sentido, la dimensión normativa busca proponer las reglas de juego en el marco de una interacción, pero también en las relaciones didácticas que se establecen en las instituciones escolares (Peña et al, 2021). Formación Universitaria Vol.…”
Section: El Sistema Normativo (Dimensión Normativa) En El Eosunclassified
“…y ¿cómo se debe enseñar? ); afectivas (regulan el aprendizaje autónomo, autoestima y compromiso); mediacional (regulan el uso de recursos al enseñar, medios técnicos y temporales); interaccionales (regulan la interacciones entre quienes intervienen en el proceso) y ecológicas ( regulan los procesos de enseñanza y aprendizaje, en la relación escuela-sociedad) (Peña et al, 2021).…”
Section: El Sistema Normativo (Dimensión Normativa) En El Eosunclassified
See 1 more Smart Citation